케이블을 사용한 드론용 공중 포획 메커니즘의 설계 및 테스트 - 정상훈(Sanghoon Jung); 응위엔 시(Nguyen Van Sy); 김병규(Byungkyu Kim); 안태영(Taeyoung An) (항공우주시스템공학회지, 2020)
We propose a capture mechanism based on the principles of fishing nets that can be mounted on the drone using cable. The gripper mechanism, mainly proposed for the drone is heavy, and is limited to catch standardized objects. In contrast, the proposed capture device in this paper is light, flexible, and can capture various types of objects from a long distance. The theoretical relationships between cables and mechanisms were analyzed. Finally, the capture device was designed and manufactured to be installed in the drone (DJI S900) to conduct capturing experiments for various objects and verify the validity. 어망의 원리를 기반으로 케이블을 사용한, 드론에 탑재할 수 있는 포획 메커니즘을 제안하였다. 최근 제안되고 있는 드론용 포획장치로 주를 이루고 있는 그리퍼(Gripper) 메커니즘은 자중이 무겁고 정형화된 물건만을 잡을 수 있다는 한계를 가지고 있다. 본 논문에서 제안하는 포획 메커니즘은 가볍고, 유연하며, 원거리에서 다양한 형태의 물건을 포획할 수 있다. 케이블과 기구장치에 대한 역학관계를 이론적으로 분석하였으며 그에 따라 기구를 설계하고 모터와 제어기를 선정하였다. 최종적으로 포획장치를 제작하고 이를 검증하기 위해 드론(DJI S900)에 설치하여 다양한 형태의 물건에 대한 포획실험을 차례로 지상과 야외 환경에서 수행하여 타당성을 입증하였다.